Voluntary exercise training improves body weight of leptin-deficient ob/ob mice by altering hepatic stearoyl-CoA desaturase 1 and deleted in breast cancer 1 protein levels - Lim, Wonchung; Hwang, Moon-Hyon; Kang, Chounghun; Kim, So Yeon; Cho, Hyeseong (Physical activity and nutrition, 2021)
[Purpose] Deleted in breast cancer 1 (DBC1) ablation causes obesity, and stearoyl-CoA desaturase 1 (SCD1) induces the biosynthesis of monounsaturated fatty acids. This study examined whether voluntary wheel running (VWR) alters SCD-1 and DBC1 protein levels in the liver of leptin-deficient ob/ob mice.[Methods] Twenty-five Ob/Ob mice were divided into two groups (ob/ob-Sed and ob/ob-Ex). The expression of DBC1 and SCD1 in the mouse liver was determined using western blotting.[Results] After 10 weeks, VWR significantly reduced body weight without affecting the fatty acid synthase and CD36 protein levels. The average daily running distance was 4.0±1.0 km/day. This improvement was associated with changes in the hepatic SCD1 and DBC1 levels. Hepatic SCD-1 protein levels increased significantly, and DBC1 protein levels decreased in ob/ob-Sed animals. On the other hand, VWR inhibited the obesity-induced increase in SCD1 expression and impaired the obesity-induced decrease in DBC1 expression in the liver of leptin-deficient ob/ob mice.[Conclusion] This is the first study showing that VWR has strong effects on hepatic SCD1 and DBC1 in ob/ob mice, and provides key insights into the effects of exercise on obesity.